2020
DOI: 10.1097/pai.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

The Immunohistochemical Pattern of Epithelial-Mesenchymal Transition Markers In Endometrial Carcinoma

Abstract: The majority of endometrial carcinoma are diagnosed at an early stage and exhibit a favorable prognosis. However, 10% to 15% of ECs recur and the majority are type II tumors which are high-grade carcinomas. The epithelial-mesenchymal transition (EMT) has been considered as a fundamental step for the development of the invasive phenotype of cancer cells. During EMT, many of epithelial surface markers, primarily E-cadherin disappear, and mesenchymal markers including N-cadherin gain. This feature resides predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…However, none of our results were statistically significant. Other authors have reported correlation between low expression of E-cadherin and higher expression of other cadherins, most importantly N-cadherin, marker of mesothelial differentiation and thus indicator of EMT (6,38,57). Our study, on the contrary, showed a positive correlation between expression of both cadherins, a phenomenon that has not yet been recognized.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, none of our results were statistically significant. Other authors have reported correlation between low expression of E-cadherin and higher expression of other cadherins, most importantly N-cadherin, marker of mesothelial differentiation and thus indicator of EMT (6,38,57). Our study, on the contrary, showed a positive correlation between expression of both cadherins, a phenomenon that has not yet been recognized.…”
Section: Discussionmentioning
confidence: 95%
“…In comparison to most other studies, we studied the average overall expression of cadherins in tumour tissue. We did not compare or distinguish between only membranous or cytoplasmic staining to take into an account a possible different intracellular location of the marker, also we did not compare the IHC reaction in centre of the tumour-to-tumour front, where differences have been most observed ( 6 , 38 ). Our N-cadherin staining has been very strong overall, having a very high mean H-score, regardless of tumour type, stage, or grade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations